A Mutant Isolated from the Cyanobacterium Synechococcus PCC7942 Is Unable to Adapt to Low Inorganic Carbon Conditions. - Yu, J. W. (1994)
Using a novel screening procedure, we have selected a new class of mutant from the cyanobacterium Synechococcus PCC7942 that fails to adapt to growth at an extremely low inorganic carbon (Ci) concentration. The mutant (Tm17) reported in this study grows normally at or above air levels of CO2 (340 [mu]L L-1) but does not survive at 20 [mu]L L-1 CO2 in air. Air-grown Tm17 cells showed properties similar to wild-type cells in various aspects of the CO2-concentrating mechanism examined. Following transfer from air levels to 20 [mu]L L-1 CO2, however, the mutant cells failed to increase their photosynthetic affinity for Ci. This results in an approximately 10-fold difference in photosynthetic affinity between the wild-type and Tm17 cells under Ci-limiting conditions [the K0.5(Ci) values were 11 and 136 [mu]M, respectively]. Further examination of factors possibly contributing to this low photosynthetic affinity showed that Tm17 cells have no inducible high-affinity HCO3- transport and do not appear to show induction of increased carboxysomal carbonic anhydrase and ribulose-1,5-bisphosphate carboxylase/oxygenase activities. It appears that a common factor, possibly relating to CO2 detection and/or induction signal, or the HCO3-transport mechanism may have been impaired in the mutant. Complementation results indicate that the mutation responsible for the phenotype has occurred in an 8- to 10-kb EcoRI genomic DNA fragment.